Axiosphere of the War Concept in the Media Discourse on the Nagorno-Karabakh Conflict - Irina V. Erofeeva (Transbaikal State University, 2021)
Linguocultural and conceptual analysis of more than 500 texts of news agencies and print media allows us to present structural and substantive characteristics of the axiosphere of the concept of War in the media discourse on the Nagorno-Karabakh conflict. The relevance of the study is due to the continuous confrontation between Armenia and Azerbaijan, despite the efforts of some countries concerned. In this situation, value reflection in relation to key aspects of the perception of the conflict objectified in the conceptualized sphere of the War of the Russian media discourse is very important. The etymological characteristic of the concept studied indicates classical opposition “war – peace” (pathology of life and its norm), which allows us to distinguish axiological dominants in the coverage of the Nagorno-Karabakh conflict in the mass media. Ideological modality of the conceptualized sphere is directly related to national interests in the context of modern geopolitical war. The scenario representation model discovered in the process of our research shows itself in the expressive paradigm “We – They”, which involves not only warring countries but also other political actors concerned. In general, the conflict discourse initiated by the media emphasizes the absolute nature of the war and its inconclusive nature, burdened by the lack of a unified response to the current situation from Armenia and Azerbaijan.